(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2005)
In low cost housing of warm humid regions where natural ventilation is usually employed, the presence of large openings will also cause unnecessary glare and heat gain of solar radiation This paper reports a preliminary study to handle glare issue without impairing natural ventilation. The use of climbing vegetation planted on a frame with fully adjusted foliage dense as shading devices is investigated. The frame is placed at the most possible position of the low cost housing and two variables, i.e. foliage porosity and leaf surface reflectance is studied using two computational simulation methods. Radiance is employed to calculate glare index after the vegetative shading and Brevent is used to assess ventilation flow rates occurred indoors toward indoors thermal comfort of the modelled housing. The study indicates that using climbing vegetation is possible for both reducing glare and supplying the required ventilation flow rates at the same time.